Photodegradation Of Methylene Blue Using Copper Oxide Prepared By Hydrothermal Method - Engku Yunus, Engku Mohamad Hafzanurudin (Universiti Sains Malaysia, 2018)
Methylene Blue (MB) has been used in many industries widely. The discharging of MB without treatment may lead to many negative effects to aquatic life. Humans are also no exception to be exposed to the negative effects of untreated MB because they need water to live. The easiest way for MB treatment is photodegradation that used sunlight that is natural source to oxidize the MB. Study continued with synthesizing Copper Oxide (CuO) catalyst for MB photodegradation using hydrothermal process that is adequate ways to obtain desirable crystals with mild condition, controllable morphology, low aggregation and high crystallinity. Hydrothermal process was varied with temperature, concentration of precursor and addition of NaOH. After that, the sample will undergo characterization which scanning electron microscope (SEM), X-Ray Diffraction (XRD), Ultraviolet–visible spectroscopy (UV-VIS) and Brunauer Emmett Teller (BET). Result from experiment illuminate size of structure bigger when concentration increase. Crystallinity also enhanced when temperature increase and addition of NaOH to precursor had produce big impact to CuO morphologies, phase and removal performance. The optimum parameter of hydrothermal process to have magnificent dye removal percentage is 0.05 M of copper acetate and urea, 134 'C and addition of 1 M of NaOH.